Ultrastructure of conidium ontogeny in Colletotrichum capsici - D.K. PUROHIT, PRAVEEN GEHLOT and (Indian Phytopathology, 2002)
The conidia and conidiogenous cells of C. capsici the incitant of fruit rot and die back of chillies were studied for their ultrastructural and developmental features employing scanning (SEM) and transmission electron microscopy (TEM). The conidiogenous cells of the fungus resembled phialides. Formation of primary conidium is holoblastic while during secondary conidium development the outer layer of phialide wall ruptures above the basal septum of primary conidium leaving a collarette, showing enteroblastic conidiogenesis. The septum at the base of each conidium is complete and Woronin bodies are absent near the septum.